Pengaruh Penggunaan Metode Imla’ Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Baca Tulis Al-Qur’an Di MTs Swasta Nahdhatul Islam Mancang - Rahman, Bayu; Setiawan, Hasrian Rudi (Al-Ulum: Jurnal Pendidikan Islam, 2023)
The aim of this research is to determine the effect of the Imla' method on student learning outcomes in Al-Qur'an reading and writing subjects at the Nahdhatul Islam Mancang Private MTs. This research uses quantitative experimental methods, with the research design used is a quasi-experimental design. The subjects in this research were school principals, teachers in the subject of reading Al-Qur'an sincerely and all class VIII students at MTs Nahdhatul Islam Mancang. This research obtained results that show that there is an influence on the Imla' method through the results of the difference in the average value of the experimental class of 84.70 after the application of student-made image media with the average value of the control class being 68.16. Meanwhile, through hypothesis testing using the T test The obtained t value is 72.17 with a significance of 0.000 0.005, so it is stated that there is an influence (Ha) accepted. After the implementation of the Imla' method, student learning outcomes in Al-Qur'an reading and writing subjects increased compared to previous results, after the implementation of the Imla' method it showed that there was an increase.